1981
DOI: 10.1128/iai.32.3.1058-1066.1981
|View full text |Cite
|
Sign up to set email alerts
|

Possible importance of macrophage-derived mediators in acute malaria

Abstract: Tumor necrosis factor, lymphocyte-activating factor, and enhanced levels of type I interferon were found in serum samples taken 2 h after mice infected with Plasmodium vinckei subsp. petteri received a small intravenous injection of endotoxin. These three mediators are among those released when mice receive an endotoxin injection 2 weeks after Mycobacterium bovis BCG or Corynebacterium parvum have been administered. There is indirect evidence that this wider range of mediators is also released in P. vinckei su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
115
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(125 citation statements)
references
References 52 publications
9
115
0
Order By: Relevance
“…A collaboration with the original laboratory studying TNF showed that TNF-rich serum fractions would indeed inhibit malaria parasite growth in vivo (99), that malaria infection would replace BCG as a primer for TNF production (99), and that the ability of a priming agent in our system paralleled its effectiveness, at the same dose, to prime for TNF generation (E. A. Carswell, personal communication). In addition, interleukin-1 (IL-1) (then called lymphocyte-activating factor) was present in the TNF-rich fractions, and roles for it in malaria were proposed (99). Thus developed the argument that TNF and similar mediators were involved in the host response to malaria parasites, a field previously the province of antibody-based mechanisms.…”
Section: Cytokine Theory Of Disease the Pre-rtnf Eramentioning
confidence: 99%
See 3 more Smart Citations
“…A collaboration with the original laboratory studying TNF showed that TNF-rich serum fractions would indeed inhibit malaria parasite growth in vivo (99), that malaria infection would replace BCG as a primer for TNF production (99), and that the ability of a priming agent in our system paralleled its effectiveness, at the same dose, to prime for TNF generation (E. A. Carswell, personal communication). In addition, interleukin-1 (IL-1) (then called lymphocyte-activating factor) was present in the TNF-rich fractions, and roles for it in malaria were proposed (99). Thus developed the argument that TNF and similar mediators were involved in the host response to malaria parasites, a field previously the province of antibody-based mechanisms.…”
Section: Cytokine Theory Of Disease the Pre-rtnf Eramentioning
confidence: 99%
“…Moreover, the ability of these agents to protect against hemoprotozoa could be predicted by how well they sensitized mice to LPS (81). A collaboration with the original laboratory studying TNF showed that TNF-rich serum fractions would indeed inhibit malaria parasite growth in vivo (99), that malaria infection would replace BCG as a primer for TNF production (99), and that the ability of a priming agent in our system paralleled its effectiveness, at the same dose, to prime for TNF generation (E. A. Carswell, personal communication). In addition, interleukin-1 (IL-1) (then called lymphocyte-activating factor) was present in the TNF-rich fractions, and roles for it in malaria were proposed (99).…”
Section: Cytokine Theory Of Disease the Pre-rtnf Eramentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the pathogen induces host cells to generate excessive amounts of pro-inflammatory cytokines, the prototypic example being tumor necrosis factor (TNF), that alter organ function and host metabolism, thus generating the disease we observe (1,2). This general concept, originally proposed to describe the severe disease caused by malaria infection (3), then sepsis (4) and influenza (5), has taken root in the mainstream, and is now often referred to as the 'cytokine storm' (6).…”
Section: Introductionmentioning
confidence: 99%